The socio-economic factors that affect the in-migration decision of street vendors in downtowm Iloilo City. - Bebis, Mary Grace C.
The lack of employment opportunities and poverty encourages migration from the rural to urban areas. This study aimed to determine the socio-economic factors that affect the in-migration decision of street vendors in downtown Iloilo City. The data were gathered through purposive sampling of sixty street vendors. The results indicated that the respondents main reason for migrating is the perceived availability of job opportunities in the city. However, information symmetry, disproved this notion. Age is the only significant factor which contributed in migration decision in this study. The younger an individual is, the higher is the tendency to migrate. Currently, there are no local policies geared towards the welfare of the street vendors. It is highly recommended that the street vendors should be relocated at one place and development of the neighboring towns of Iloilo City be affected to curb the influx of in-migration.